A critical review on metabolomic analysis of milk and milk products. (15th October 2020) - Sen, Chandrakanta; Ray, Pinaki Ranjan; Bhattacharyya, Mahasweta
Abstract : Metabolomics deals with the identification and quantification of the small molecules involved in metabolic reactions. It has recently been used to understand the nutritional quality and authenticity of milk and milk products. Various analytical techniques such as nuclear magnetic resonance spectroscopy, liquid chromatography–mass spectrometry, gas chromatography–mass spectrometry and ultra‐performance liquid chromatography–quadrupole time‐of‐flight mass spectrometry have been successfully employed to identify and quantify the metabolites present in milk and milk products. This review focuses on the recent advances in metabolomics for quality and safety analyses of milk and milk products. Abstract : Graphical abstract of milk metabolomics.